How do you use implicit differentiation to find $\frac{{d}^{2}y}{{dx}^{2}}$ of ${x}^{3}+{y}^{3}=1$

Donna Flynn
2022-07-23
Answered

How do you use implicit differentiation to find $\frac{{d}^{2}y}{{dx}^{2}}$ of ${x}^{3}+{y}^{3}=1$

You can still ask an expert for help

yermarvg

Answered 2022-07-24
Author has **19** answers

By implicitly differentiating twice, we can find

$\frac{{d}^{2}y}{{dx}^{2}}=-\frac{2x}{{y}^{5}}$

First, let us find $\frac{dy}{dx}$

${x}^{3}+{y}^{3}=1$

by differentiating with respect to x

$\Rightarrow 3{x}^{2}+3{y}^{2}\frac{dy}{dx}=0$

by subtracting $3{x}^{2}$

$\Rightarrow 3{y}^{2}\frac{dy}{dx}=-3{x}^{2}$

by dividing by $3{y}^{2}$

$\Rightarrow \frac{dy}{dx}=-\frac{{x}^{2}}{{y}^{2}}$

Now, let us find $\frac{{d}^{2}y}{{dx}^{2}}$

by differentiating with respect to x

$\Rightarrow \frac{{d}^{2}y}{{dx}^{2}}=-\frac{2x\cdot {y}^{2}-{x}^{2}\cdot 2y\frac{dy}{dx}}{{\left({y}^{2}\right)}^{2}}=-\frac{2x({y}^{2}-xy\frac{dy}{dx})}{{y}^{4}}$

by plugging in $\frac{dy}{dx}=-\frac{{x}^{2}}{{y}^{2}}$

$\Rightarrow \frac{{d}^{2}y}{{dx}^{2}}=-\frac{2x[{y}^{2}-xy(-\frac{{x}^{2}}{{y}^{2}})]}{{y}^{4}}=-\frac{2x({y}^{2}+\frac{{x}^{3}}{y})}{{y}^{4}}$

by multiplying the numerator and the denominator by y

$\Rightarrow \frac{{d}^{2}y}{{dx}^{2}}=-\frac{2x({y}^{3}+{x}^{3})}{{y}^{5}}$

by plugging in ${y}^{3}+{x}^{3}=1$

$\Rightarrow \frac{{d}^{2}y}{{dx}^{2}}=-\frac{2x}{{y}^{5}}$

$\frac{{d}^{2}y}{{dx}^{2}}=-\frac{2x}{{y}^{5}}$

First, let us find $\frac{dy}{dx}$

${x}^{3}+{y}^{3}=1$

by differentiating with respect to x

$\Rightarrow 3{x}^{2}+3{y}^{2}\frac{dy}{dx}=0$

by subtracting $3{x}^{2}$

$\Rightarrow 3{y}^{2}\frac{dy}{dx}=-3{x}^{2}$

by dividing by $3{y}^{2}$

$\Rightarrow \frac{dy}{dx}=-\frac{{x}^{2}}{{y}^{2}}$

Now, let us find $\frac{{d}^{2}y}{{dx}^{2}}$

by differentiating with respect to x

$\Rightarrow \frac{{d}^{2}y}{{dx}^{2}}=-\frac{2x\cdot {y}^{2}-{x}^{2}\cdot 2y\frac{dy}{dx}}{{\left({y}^{2}\right)}^{2}}=-\frac{2x({y}^{2}-xy\frac{dy}{dx})}{{y}^{4}}$

by plugging in $\frac{dy}{dx}=-\frac{{x}^{2}}{{y}^{2}}$

$\Rightarrow \frac{{d}^{2}y}{{dx}^{2}}=-\frac{2x[{y}^{2}-xy(-\frac{{x}^{2}}{{y}^{2}})]}{{y}^{4}}=-\frac{2x({y}^{2}+\frac{{x}^{3}}{y})}{{y}^{4}}$

by multiplying the numerator and the denominator by y

$\Rightarrow \frac{{d}^{2}y}{{dx}^{2}}=-\frac{2x({y}^{3}+{x}^{3})}{{y}^{5}}$

by plugging in ${y}^{3}+{x}^{3}=1$

$\Rightarrow \frac{{d}^{2}y}{{dx}^{2}}=-\frac{2x}{{y}^{5}}$

asked 2022-04-16

How do we go from

$\frac{1}{1+\left(\frac{x}{2}\right)+\left(\frac{{x}^{2}}{3}\right)+\left(\frac{{x}^{3}}{4}\right)+\dots}$

asked 2022-04-21

Verify that the following function ${y}^{2}={e}^{\left(2x\right)}+C$ is a solution of the ODE: $y{y}^{\prime}={e}^{\left(2x\right)}$

asked 2020-10-26

For each of the following series, using no tests besides the nth Term and Comparison Tests, determine whether the series converges, diverges to $\pm \mathrm{\infty}$ , or diverges, not to $\pm \mathrm{\infty}$

$\sum \frac{n-1}{{n}^{2}-1}$

asked 2022-07-10

What steps would I take or use in order to use the intermediate value theorem to show that $\mathrm{cos}x=x$ has a solution between $x=0$ and $x=1$?

asked 2022-01-22

Find the series:

$\sum _{n=1}^{\mathrm{\infty}}({(1+\frac{1}{n})}^{n}-e)$

asked 2022-04-23

Show that the change of variables $x=2u+v,y=3u+v$ transforms the linear system

$\{\begin{array}{rl}{x}^{\prime}(t)& =\phantom{3}x-2y\\ {y}^{\prime}(t)& =3x-4y\end{array}$

into

$\{\begin{array}{rl}{u}^{\prime}(t)& =-2u\\ {v}^{\prime}(t)& =-v\end{array}$

Verify that the u-axis maps to the line$y=\frac{3}{2}x$ and the v-axis maps to the line $y=x$ .

I thought for this I would just have to plug the substitutions into x'(t) and y'(t) but when doing this I receive

$\{\begin{array}{rlr}{u}^{\prime}(t)& =2u+v-2(3u+v)\phantom{\rule{-15pt}{0ex}}& =-4u-v\\ {v}^{\prime}(t)& =3(2u+v)-4(3u+v)\phantom{\rule{-15pt}{0ex}}& =-6u-v\end{array}$

into

Verify that the u-axis maps to the line

I thought for this I would just have to plug the substitutions into x'(t) and y'(t) but when doing this I receive

asked 2022-06-29

What is the average value of a function $\mathrm{sin}(X)$ on the interval $[0,\pi ]$?